Evaluation of responsiveness to non-clinical demands of patients in Iran: a quantitative study on the university hospitals in Bushehr - Modarresi, Mahboobeh-sadat; Omranikhoo, Habib; Modarresi, Mozhgan; motamed, Niloofar (Social Determinants of Health, 2017)
Background: Responsiveness along with health promotion and financial risk protection plays a pivotal role in health systems. The present study aimed to examine responsiveness in hospitals affiliated to Bushehr University of Medical Sciences, in the south-west of Iran. Methods: In a cross-sectional study, the statistical population consisted of the patients referring to two university hospitals in Bushehr, namely Persian Gulf Hospital and Bushehr Heart Center. In total, 402 patients were selected using the stratified random sampling method. Data was collected using a demographic questionnaire and the validated Persian version of the standard World Health Organization questionnaire on health system responsiveness to assess responsiveness level during 2015. Results: Responsiveness level was statistically different between the two hospitals (2.3±0.58 and 2.7±0.50, respectively). In general, “access to social support” (3±0.93) and “choice of health provider” (1.7±0.93) obtained the highest and lowest scores. Apart from “confidentiality” and “access to social support,” a statistically significant difference was observed in other domains (dignity”, “autonomy”, “communication”, “quality of basic amenities”, “choice of health care provider”, and “prompt attention” (between the two hospitals. Conclusion: University hospitals studied had an average performance regarding responsiveness. It seems necessary to pay more attention to two domains of responsiveness including choice of health provider and autonomy in the hospitals.